Ultrastructure of the terminal parts of the protonephridial system of Baltoplana magna (Platyhelminthes, Kalyptorhynchia, Schizorhynchia, Karkinorhynchidae) - Rohde, K.; Watson, N. A. (Malaysian Journal of Science, 1994)
Protonephridial capillaries of Baltoplanamagnalack a septate junction. The proximal canal cell overlaps the distal part of the terminal cell but does not contribute to the weir (filtration apparatus) of the flame bulb. Each perikaryon of a terminal cell forms a single flame bulb with a single row of longitudinal ribs that contain bundles of microtubules. Internal leptotriches are notpresent. The flame bulb of Baltoplana resembles that of all other turbellalian rhabdocoels examined (single row of ribs, microtubules, no internal leptotriches), but differs from that of some in having perikarya forming single flame bulbs. Phylogenetic implications are discussed. ABSTRAK Kapilari protonefridium bagi.Baltoplana magna tidak mempunyai simpang berseptum. Sel saluran proksimal bertindak dengan bahagian distal sel terminal tetapi tidak merupakan weir (radas penurasan) pada bebuli nyala. Setiap perikarion sel terminal membentukkan satu bebuli nyala tunggal dengan satu baris tetulang longitudinal yang mengandungiberikat-ikatmikrotubul. Leptotrikes tidak wujud. Bebuli nyala dalam Baltoplana merupai yang terdapat padakesemua ’turbellarian rhabdocoels’ yang telah dikaji (iaitu, satu baris tetulang, mikrotubul, tanpa leptotrikes internal), tetapi berbeza dari beberapanya dengÃ¡n kepunyaan perikarion-perikarion yang membentukkan bebuli nyala. Implikasi filogenetik dibincangkan. (Baltoplana magna, Platyhelminthes, Kalyptorhynchia, protonephridia, phylogeny)